Analisa Risiko Unit Kerja Operasional Terminal Petikemas Mustika Alam Lestari - Purnomo, Aris Dwi; Setyaji, Ridho; Helmiansyah, Ramadhan; Saddam, Al Hanief; Ladesi, Vivian; sahara, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The purpose of this study was to determine the risk analysis at Terminal Mustika Alam Lestari container is one of the places to send or store goods to be sent by sea transportation which has a very high risk because every job can cause potential harm if something unwanted happens, data collection techniques through interviews and field observations where there are 3 outlines of risk, namely long queues are most influential because they hamper operational activities followed by tool damage which has a moderate risk and then being hit and run over has the lowest risk